Analysis of Factors Associated with IUD KB Acceptors at the Health Center Poyawa Besar - Strahmawati Hamzah; Hamzah B (Politeknik Karya Persada Muna, 2022)
Baground: The high rate of population growth is the main problem faced by Indonesia in the field of population. Uncontrolled population growth rate can lead to health problems and population problems. One of the efforts made by the government to suppress the rate of population growth is the long term family planning program such as the IUD. In fact, the use of IUDs is still lacking because it is influenced by low knowledge and lack of husband support. The purpose of this study was to determine the factors associated with IUD KB acceptors at the Health Center Poyawa Besar in Kotamobagu. Method: The type of research used is analytic observational with a cross sectional study design. The sample in this study was 51 respondents, obtained by accidental sampling technique. Data were collected using a questionnaire and analyzed by univariate and bivariate with chi square test. Results: The results showed that there was a relationship between the level of knowledge (p = 0.001) and husband’s support (p = 0.000) with IUD family planning acceptors at the Health Center Poyawa Besar in Kotamobagu. Knowledge and the husband's support can influence a person in choosing contraceptives to use. Conclusions: Factors related to IUD family planning acceptors at the Puskesmas Pembantu Poyowa Besar are the level of knowledge and husband's support. Keywords: Knowledge, husband support, family planning